PENGEMBANGAN MULTIMEDIA UNTUK MENINGKATKAN KEAKTIFAN SISWA DALAM MATA PELAJARAN PAI KELAS VII DI SMP IT AL-QONITA PALANGKA RAYA IMPLEMENTASI MODEL KEMP - Melta Ayunitha; Jasiah Jasiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to develop multimedia-based learning media in the material of prostration of gratitude, sahwi and tilawah to increase the activeness of seventh grade students at Al-Qonita Integrated Islamic Junior High School Palangka Raya. This research uses the Research and Development (R&D) method with the Kemp model. Data were collected through observation, interviews, questionnaires and documentation. Research instruments to test the feasibility of media, namely media expert validation instruments, material expert validation instruments, teacher and student questionnaires. The results of this study indicate that the feasibility of media based on the results of media expert validation obtained a score of 83% with very good criteria. Meanwhile, the validation results from material experts obtained a score of 78% with good criteria. Furthermore, the results of the teacher questionnaire obtained a score of 86% with very good criteria. While the results of student questionnaires obtained a score of 93.3% with very good criteria. In conclusion, multimedia-based learning media is very effective in increasing student activeness in PAI learning, from the results of the questionnaire that researchers get from educators also state that the media used is very interesting and makes students look active in learning.